2006
DOI: 10.1532/lh96.06012
|View full text |Cite
|
Sign up to set email alerts
|

Immature Platelet Fraction as a Predictor of Platelet Recovery Following Hematopoietic Progenitor Cell Transplantation

Abstract: The immature platelet fraction (IPF) as determined by the Sysmex XE-2100 is a rapid automated measure of the least mature component of the platelet population and is thought to correlate with thrombopoietic activity of the marrow. We investigated the ability of IPF to predict platelet recovery following hematopoietic progenitor cell (HPC) transplantation. IPF was compared to standard parameters of hematopoietic recovery, including the immature reticulocyte fraction (IRF), an early predictor of recovery. Fifty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 2 publications
6
56
3
Order By: Relevance
“…The previously reported reference interval using the Sysmex XE-2100 for healthy adults is between 0.4% and 10% [1,9,[22][23][24][25][26][27]. The limitations of these reported reference intervals are: 1) small control groups, including less than 150 individuals, 2) incorrect application or lack of application of the CLSI guideline for determining reference intervals, and 3) exclusion of pediatric individuals in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previously reported reference interval using the Sysmex XE-2100 for healthy adults is between 0.4% and 10% [1,9,[22][23][24][25][26][27]. The limitations of these reported reference intervals are: 1) small control groups, including less than 150 individuals, 2) incorrect application or lack of application of the CLSI guideline for determining reference intervals, and 3) exclusion of pediatric individuals in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The IPF% can be a useful parameter to estimate platelet recovery after peripheral blood stem cell transplant and chemotherapy, thereby reducing the number of unnecessary platelet transfusions. Following peripheral blood stem cell transplant in adults, the IPF% value rises 1-2 days prior to the increment in platelet count [23,25]. Saigo et al [30] observed platelet recovery within 3-7 days after the day of peak IPF% in pediatric patients with various malignant disorders after chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] The Sysmex XE2100 identifies the IPF using a combination of a proprietary fluorescent RNA stain (which preferentially binds young platelets) and light scatter characteristics. [25][26][27] The immature platelet count was derived from the platelet count (measured in the XE2100) and the IPF %.…”
Section: Immature Platelet Fractionmentioning
confidence: 99%
“…This question was addressed in the present study by direct measurement of the number of circulating new platelets (by the IPF in a Sysmex XE-2100, which is based on the higher messenger RNA content of young compared with old platelets [25][26][27] ). We demonstrated that discontinuation of clopidogrel did not result in the release of young platelets ( Figure 6).…”
mentioning
confidence: 99%
“…This is why the devices currently available, despite claims to the contrary, have a poor specificity for "reticulated" platelets even if the addition of RNAse is used as evidence and somewhat reduces the signal. Therefore, the expectations in the follow-up studies to the original publications with manual measurement on the flow cytometer [6][7][8][9][10][11][12] have not been met, or only partially, on routine equipment with a reticulocyte channel [13][14][15][16][17][18], since the Spearman correlation coefficients are only at about 0.6. This clinically valuable parameter of the increased premature platelet release has therefore rarely been incorporated into clinical decisions in the differential diagnosis of thrombocytopenia.…”
Section: Livermentioning
confidence: 99%